EFFECTS OF HYDRAZONE COMPOUND DERIVED FROM 4-AMINO ANTIPYRINE AND BUTANEDIONE AND ITS Ni (II) COMPLEX ON HAEMATOLOGICAL AND DIFFERENTIAL BLOOD COUNT OF ALLOXAN INDUCED DIABETIC RATS - Agbo, Ndidiamaka Justina; Ukoha, Pius Oziri (FUDMA Journal of Sciences, 2024)
In this study, the effect of Schiff base compound derived from 4-Aminoantipyrine and 1-phenylbutan-1,3-dione and its Ni(II) complex, on the haematology indices of diabetic rats was investigated. A single intraperitoneal injection of Alloxan (120 mg/kg body weight), induced diabetes. The rats were treated with 200 and 400 mg/kg of body weight of 3-[2-(1,5-Dimethyl-3-oxo-2-Phenyl-2,3-Dihydro-1H-Pyrazol-4-yl)Hydrazinylidene]-1-Phenylbutanedione (HL) and its Ni(II) complex ([Ni(HL)2]Cl2) respectively for 14 days, following which they were humanely sacrificed under chloroform. A heart puncture was used to collect blood, and some of the blood samples were analyzed to evaluate white blood cell (WBC), red blood cell (RBC) counts, packed cell volume (PCV) and hemoglobin (Hb) concentration, and differential blood count profiles. Red blood cells, hemoglobin and packed cell volume concentrations in rats treated with HL and [Ni(HL)2]Cl2 in (low and high doses) increased when compared with untreated group B diabetic rats. The Eosinophils, Monocytes, and Lymphocytes were observed to be bad in the diabetic rats; this was significantly better in the treatment groups. HL and [Ni(HL)2]Cl2 have therapeutic promise as functional medicines against diabetes and complete blood count alterations linked to diabetes mellitus, as demonstrated by these studies. In the diabetic group, oxidative stress results in RBC dysfunction, platelet destruction, and tissue injury. These affect the functions of blood cells and the haemostatic parameters which may lead to various complications. As a result, these substances may be used as medication therapy for diabetes since they lower the glucose concentration without alterations in blood cells.